School violence and pedagogical mediation in basic education students (Revista Innova Educación, 2021)
The school violence is a subject that has aroused interest in its study, because it has permeated society through time at school, therefore, the objective is design a strategy to prevent future misunderstandings among fifth grade kids of the Marco Antonio Franco Rodriguez school of Villavicencio, Colombia. For the research, a descriptive research method was used with a mixed qualitative and quantitative methodology, the technique for the collection of information was done through an interview and a survey directed to the students, showing the following results: The witnesses show that the most repeated problems are teasing in class, stealing things and hitting in the classroom; the victims say that they almost always lose something and have been teased. The behaviors of highest incidence on the part of the aggressor are teasing in the classroom, pushing in lines, and hiding or taking things. It can be concluded that mediation is an opportunity for change with no losers.
Keywords: Aggressors; pedagogical mediation; victims; school violence